Association of Aortic Stiffness and Cognitive Decline: A Systematic Review and Meta-Analysis - Liu, Qian; Fang, Jinghuan; Cui, Chaohua; Dong, Shuju; Gao, Lijie; Bao, Jiajia; Li, Yanbo; Ma, Mengmeng; Chen, Ning; He, Li (Frontiers in Aging Neuroscience, 2021)
Background: Increased aortic stiffness has been found to be associated with cognitive function decline, but the evidence is still under debate. It is of great significance to elucidate the evidence in this debate to help make primary prevention decisions to slow cognitive decline in our routine clinical practice. Methods: Electronic databases of PubMed, EMBASE, and Cochrane library were systematically searched to identify peer-reviewed articles published in English from January 1, 1986 to March 16, 2020 that reported the association between aortic stiffness and cognitive function. Studies that reported the association between aortic pulse wave velocity (PWV) and cognitive function, cognitive impairment, and dementia were included in the analysis. Results: Thirty-nine studies were included in the qualitative analysis, and twenty-nine studies were included in quantitative analysis. The aortic pulse wave velocity (PWV) was inversely associated with memory and processing speed in the cross-sectional analysis. In the longitudinal analysis, the high category of aortic PWV was 44% increased risk of cognitive impairment (OR 1.44; 95% CI 1.24-1.85) compared with low PWV, and the risk of cognitive impairment increased 3.9% (OR 1.039; 95% CI 1.005-1.073) with per 1 m/s increasing in aortic PWV. Besides, meta-regression analysis showed age significantly increased the association between high aortic PWV and cognitive impairment risk. Conclusion: aortic stiffness measured by aortic PWV was inversely associated with memory and processing speed, and could be an independent predictor for cognitive impairment, especially for older individuals.